DETERMINATION OF FLASH CLOUD – GROUND DENTITY APPROACHED BY GEOSTATISTIC - Okqye, Igosius; Kurnianto, Rudi; Danial, Danial (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2023)
Pontianak City is an area located in the equatorial area which has an area of 107.82 km2 and consists of 6 districts. Because it is located in the equatorial area, it results in the growth of convective clouds in Pontianak City with the potential for lightning and heavy rain. The purpose of this study was to obtain interpolation modeling of lightning strike density in Pontianak City using geostatistical approaches, namely kriging and IDW methods ((Inverse Distance Weighted). The results of the two methods are compared to obtain feasible parameters to use to determine the density of lightning strikes. Based on the results of the analysis, the kriging method with spherical type is better than the exponential and gaussian methods, while for the IDW method power 3 is better than power 1 and 2. The average lightning strikes per grid in the Pontianak area ranges from 2 to 22 strikes per grid/km2/year. The highest strike on the Pontianak Kota grid with 22 strikes and the lowest on the Southeast Pontianak grid with 2 strikes. Meanwhile, based on the contour map of lightning strike density in the Pontianak City area using kriging and IDW methods, the results for the highest lightning strike range are Pontianak City with a total of 5-20 strikes. As for the lowest lightning strike range, namely Southeast Pontianak with a total of 2-9 strikes.